2015
DOI: 10.7888/juoeh.37.111
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Functional Outcome Between Early and Delayed Internal Fixation Using Volar Locking Plate for Distal Radius Fractures

Abstract: : The purpose of this study was to assess the effect of timing (Early (E) group vs Delayed (D) group) of internal fixation for distal radius fractures on forearm and wrist function in patients who underwent the surgery. The subjects were one hundred six patients who had extra-articular fractures of the dorsally displaced distal radius and were treated with a volar locking plate. The subjects were divided into two groups: E group (Operation on the day of injury or the next day, n = 76 ; and the D group (Operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 15 publications
(15 reference statements)
0
21
0
Order By: Relevance
“…Yamashita et al. (2015) performed a retrospective study of extra-articular DRFs, and found no difference in functional results between early and delayed fixation at 1 year of follow-up. Our study included intra-articular fractures and had a longer follow-up time, possibly explaining the difference.…”
Section: Discussionmentioning
confidence: 99%
“…Yamashita et al. (2015) performed a retrospective study of extra-articular DRFs, and found no difference in functional results between early and delayed fixation at 1 year of follow-up. Our study included intra-articular fractures and had a longer follow-up time, possibly explaining the difference.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome was RoM [10,22]. The motion angles of the wrist and forearm on the injured side were measured by an occupational therapist who was certified at the Hand Surgery Evaluation Method Workshop in Japan.…”
Section: Primary Outcome: Arc Of Wrist Flexion-extensionmentioning
confidence: 99%
“…We examined the feasibility of Ghost for clinical use during a preliminary study involving a small sample. Age and body mass index (BMI) were selected as independent variables for stratified analysis, as these variables have been found to affect ROM improvements with VR therapy in DRF patients in previous reports [10,22]. For instance, treatment outcomes with the VR system are affected by age and cognitive function [25].…”
Section: Analytic Strategiesmentioning
confidence: 99%
“…Early surgery shows superior outcomes and is recommended in most cases [ 8 , 9 , 10 , 11 ]. However, some studies have shown that delayed fixation affects only short-term outcomes and is indistinguishable in long-term functional results [ 12 , 13 ]. Moreover, there is no information about the effect of delayed fracture fixation on the difficulty of intraoperative surgical operation and acute postoperative periods.…”
Section: Introductionmentioning
confidence: 99%